Clinical implications of perineural invasion in patients with colorectal cancer. Issue 17 (April 2020) - Hu, Gang; Li, Liang; Hu, Kaibing
Abstract : Abstract: Perineural invasion (PNI) is a prominent characteristic of multiple solid tumors and indicates poor prognosis. Previous data concerning the impact of PNI on prognosis of patients with colorectal cancer (CRC) are conflicting, and little is known about risk factors of PNI. The aim of our study was to reveal the clinical implication of PNI on survival outcome and identify risk factors for the poor prognosis in patients with CRC. We retrospectively reviewed 627 patients who were diagnosed with CRC and underwent curative surgical resection. The differences in several clinicopathologic characteristics were compared between PNI positive and PNI negative groups. Multivariate logistic regression analysis was performed to identify predictors of CRC with PNI. Five-year overall survival (OS) and disease-free survival (DFS) were calculated using the Kaplan–Meier method, and the difference in survival rate was assessed by the log-rank test. The variables that had prognostic potential, as indicated by univariate analyses, were subjected to multivariate analyses with the Cox proportional hazards regression model. PNIs were identified in 79 patients (12.6%). Age, T classification, N classification, M classification, UICC classification, and lymphovascular invasion were significantly associated with PNI. Multivariate logistic regression analysis demonstrated that only lymphovascular invasion was a predictor of PNI. Pathologic evidence of PNI was not associated with survival outcome (the 5-year OS [ P  = .560] and DFS [ P  = .083]). Cox proportional hazards regression model revealed that age and N2/3 classification were independent prognostic factors for poorer OS and DFS. M1 stage (95% confidence interval [CI] = 0.228–0.585, P  = .000), III/IV stage (95% CI = 0.335–0.920, P  = .022), and number of sampled lymph nodes (95% CI = 0.951–0.987, P  = .001) were independently prognostic for poorer OS, while history of other malignancy (95% CI = 1.133–2.813, P  = .012) was identified as an independent prognostic factor for poorer DFS. Our study indicates that PNI is not an independent poor prognostic factor in patients with CRC and those patients with PNI may not benefit from postoperative adjuvant chemotherapy.